Meningkatkan Self-Esteem Siswa Melalui Model Pembelajaran Learning Cycle 7E Berdasarkan Kemampuan Awal Matematis - Firdaus Firdaus (ARITHMETIC: Academic Journal of Math, 2019)
This research is a quasi-experimental research. The purpose of the study was to present a picture of the increase in self-esteem of students who obtained the 7E learning cycle learning model compared to students who obtained conventional learning based on student KAM. This research was conducted at a Junior High School in Serang Regency, Banten Province. Data collection techniques in research is through pretest and posttest. Data analysis was performed through a self-esteem scale score with the Mann-Whitney U test. The results showed that the increase in self-esteem of students who obtained the 7E learning cycle learning model was better than that of students who obtained conventional learning models in the medium KAM category. Whereas in the low and high KAM categories there is no difference in the increase in self-esteem of students who get the 7E learning cycle compared to students who get conventional learning.